Incidence of the usage of innovative games in the Teaching - Learning process of english with the students of fourth basic A and B at Angel Polibio Chaves School, during the year 2004 - 2005 - Noroña, Alexandra (2006)
During a period of time teachers has been looking for new strategies to wake the interest of the students in the English learning and do not continue with the traditional methods, in this way we use the INNOVATIVE GAMES as a new strategy for the students in order to learn in an active and funny way. Chapter I focuses on a brief description about the need to give to the students an active learning through new strategies, new ideas that awake the interest in English learning as a foreign language. We show how to usage of innovative games incidence in the Teaching-learning process of English in the 8-9 years old children of fourth basic year at Angel Polibio Chaves School. We can see how the traditional methodology have influenced in the English learning an which ways the innovative games can help the students in their learning process. The importance of the usage of innovative games as the best vehicle to make a positive interaction between teachers and students. So the use of innovative games are very useful as reinforcement of the four skill of the language: reading, speaking, listening and writing, in the same way developing grammar activities. We also support the hypothesis that the innovative games are consider a valuable strategy in the teaching of English as a foreign language. We focus on elements and principles of the teaching learning process, a clarification of what you tent to do and a mark of reference to organize the formative process, so the formula of teaching objectives is responsibility and decision from the teacher that is in front of a group of students. The teaching activities that focus on grammatical accuracy maybe quite different from those that focus on communicative skill, the learning process that refers to the formal study of language rules and is a conscious...